G-Exos: A wearable gait exoskeleton for walk assistance - Zorkot, Mouhamed; Dac, Léa Ho; Morya, Edgard; Brasil, Fabrício Lima (Frontiers in Neurorobotics, 2022)
Stroke is the second leading cause of death and one of the leading causes of disability in the world. According to the World Health Organization, an estimated 11 million people suffer a stroke each year. The cost of the disease is exorbitant, and the most widely used treatment is conventional physiotherapy. The use of technology optimizes rehabilitation, but it has limitations such as robustness, low usability, and limited long-term results. To overcome this problem, the goal of this work was to develop a low-cost ankle orthosis, the G-Exos, a wearable exoskeleton that provides an increase in motor capacity, aiding gait by assisting in the movements of dorsiflexion, plantar flexion and ankle stability. This was done through a mixed system: active, using motor and hardware; and passive, using natural gait biomechanics to provide near-natural movement. The system was validated with 10 volunteers with foot drop: 7 with stroke, 2 with incomplete spinal cord injury (SCI) and 1 with acute inflammatory transverse myelitis (ATM). The G-Exos showed the expected functionality for gait assistance. A Friedman test showed that there was a significant difference in dorsiflexion amplitude for the dropped foot group with the use of the G-Exos compared to gait without the use of the G-Exos, (x² (3) = 98.56, p < .001). In addition, there was also a significant difference in ankle eversion and inversion for the same group when comparing walking with G-Exos and without using it, both on the ground (x² (3) = 36.12, p < .001) . In an overall context, it was possible to develop a lightweight and flexible assistive technology device and detect the gait phase accurately, providing better human-machine interaction. With the use of the G-Exos, a therapy with a greater capacity to deal with gait disorders, greater usability, and a more effective motor and neurological recovery is intended, resulting in a better quality of life for these patients, in addition to use in activities of daily living.